INSECT DIVERSITY IN MANGROVE ECOSYSTEMS IN PAYUM BEACH, MERAUKE REGENCY, PAPUA - Sembiring, Jefri; Saleky, Dandi; Merly, Sendy Lely; Pangaribuan, Rosa Delima; Mendes, Johanna (Universitas Medan Area, 2024)
Mangrove forest is a permanent habitat and transit area for various fauna. In the mangrove community, it forms a mixed habitat between terrestrial and aquatic fauna groups. This study aims to analyze the composition of mangrove species and the abundance of insects. There are 3 research station on the mangrove forest ecosystem on Payum beach. Sampling was carried out using the Line Transect method, starting with making a line transect (50 meters) on the outermost mangrove stands and pulling them inland. On each transect line a plot measuring 10 x 10 m is placed, in each of which 5 subplots/quadrants measuring 1 x 1 m are placed. Each transect line consist of 3 plots and 15 sub-plots will be obtained, so there are a total of 45 sub-plots. Based on the research results, it was found that several types of macrobenthos live abundantly and are associated with mangrove ecosystems, such as Terebralia palustris, Terebralia semistriata, Nerita sp., Cassidula angulifera, Cerithidea sp., Telescopium telescopium. Four species of mangroves are found on Payum Beach, Merauke Regency, South Papua Province, namely Avicennia alba, Rhizophora apiculate, Sonneratia alba, and Aegialitis annulata. The insect diversity index in the mangrove forest on Payum Beach in Merauke is H'=2.61, which indicates that the environmental conditions of Payum Beach are still quite good and insect diversity is in the medium category. The evenness index of 0.42 is included in the medium category because human activities vary, and the dominance index is 0.63 because the Payum Beach mangrove forest has various types of insects with moderate dominance.